Population Based Study of Cervical Cancer Screening in Bharatpur, Nepal - Sherpa, Ang Tshering; Karki, Balman Singh; Sundby, Johanne; Nygard, Mari; Franceschii, Silvia; Clifford, Gary (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
Cervical cancer is the most common form of cancer among women in developing countries. Hospital based data in Nepal also showed cervical cancer is most commonly occurring cancer among women in Nepal. Pap smear is the very significant screening test for reduction of incidence and mortality from cervical cancer but many developing countries failed to obtain high coverage of target population. Hence failed to achieve major impact of cervical cancer screening. National guidelines for cervical cancer and prevention in Nepal is formulated in 2010 and set target population age range of 30-60 with 50% coverage of target population with in a five years span. This study was aimed to elicit baseline survey of cervical cancer screening in a locale where resource for cervical cancer screening is easily available. Population based cross sectional study was done from October 2006 to March 2007. 1547 ever married women aged 16–59 were selected with cluster randomization procedure from Bharatpur municipalities, where BPKMCH (BP Koirala Memorial Cancer Hospital) is located. Free cervical cancer screening was conducted in collaboration with International Agency for Research on Cancer (IARC) France and BPKMCH. Ethical clearance was obtained from Nepal Health Research council. Interviews were performed using a standard questionnaire to elicit required information. Out of 1033 participants 394 were 16-29 years old. Among them 117 (30%) had at least one Pap test prior coming to the clinic. 16(4%) were age 16-19, 42(11%) were age 20-24 and 59 (15%) were age 25-29. This concludes Present opportunistic cervical cancer screening in Bharatpur is directed towards screening significant proportion of women with less risk. DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.11994 Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015 page : 3-8